2022
DOI: 10.3389/fpsyt.2022.827076
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Differences in Healthcare Workers Exposed to Different Risks During the Coronavirus Disease 2019 Pandemic

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic has caused a significant impact on the physical and mental health of healthcare workers. This study assessed the psychological status of healthcare workers who were exposed to different risk-levels in China and explored the factors that affected their mental health.MethodsDemographic, occupational characteristics, and mental health measurements were collected from 810 workers in 41 hospitals in China, through online questionnaires from February 11 to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(91 reference statements)
2
1
1
1
Order By: Relevance
“…Notably, among nurses only, women no longer reported more mental health problems than men, and the relation between contact with COVID-19 patients and mental health became non-significant only among men. It has been previously found that, in comparison to other HCWs, nurses face a heightened risk of experiencing mental health issues during the COVID-19 pandemic (Zhang et al, 2022), with some studies finding an even more increased risk among women compared to men in this group (Simonetti et al, 2021;Varghese et al, 2021), which is not consistent with our findings. In our sample there was considerable overlap between gender and occupation roles since most nurses (84.4%) were women.…”
Section: Relation Of Covid-19-relevant Exposures At the Country Level...contrasting
confidence: 99%
“…Notably, among nurses only, women no longer reported more mental health problems than men, and the relation between contact with COVID-19 patients and mental health became non-significant only among men. It has been previously found that, in comparison to other HCWs, nurses face a heightened risk of experiencing mental health issues during the COVID-19 pandemic (Zhang et al, 2022), with some studies finding an even more increased risk among women compared to men in this group (Simonetti et al, 2021;Varghese et al, 2021), which is not consistent with our findings. In our sample there was considerable overlap between gender and occupation roles since most nurses (84.4%) were women.…”
Section: Relation Of Covid-19-relevant Exposures At the Country Level...contrasting
confidence: 99%
“…Depression, anxiety, and stress were the most studied mental health conditions. Most studies reported a high (prevalence ≥ 50%) vulnerability to these three mental conditions (21,22,36,39,43,44,47,57,62,74,86) This finding is consistent with previous studies (95,96).On the contrary, Jörns-Presentati et al, (94), reported a lower prevalence (29.0%) of depression. According to the WHO, the pandemic spiked with a 25% increase in the prevalence of mental disorders worldwide (7,95,96).…”
Section: Prevalence Of Mental Disorders During the Covid-19 Pandemicsupporting
confidence: 86%
“…This finding is in line with the WHO observation that depression and anxiety disorders were higher in places with higher COVID-19 cases (113,114). This is supported by previous studies that showed that the fear and anxiety associated with the threatening numbers of cases and death in people's neighborhood was seen earlier to increase the serious risk for mental breakdown (115) since a perceived or actual increase in the risk of exposure to COVID-19 was a major driver for adverse mental health (48,74). Some studies reported that poor psychosocial support increased the prevalence and severity of mental health disorders among vulnerable population groups such as strictly isolated or heavily quarantined persons (116), individuals who lacked family support or care (117), elderly persons in need of nursing care (49,118), persons at risk of losing their jobs (33), persons without financial and social support (24,30,42,47,54,63,69,77,119), divorced persons (23,65,79), and relatives and guardians of sick persons (84).…”
Section: Factors Associated With Mental Health Disorder Prevalencesupporting
confidence: 71%
See 1 more Smart Citation
“…Nesse contexto, qualquer fator de stress adicional pode desencadear ou agravar a ansiedade de cada indivíduo e afetar a sua capacidade cognitiva (3) (4). Na era da COVID-19, os profissionais de saúde, diretamente e indiretamente envolvidos no combate à pandemia, estiveram diariamente expostos ao risco de serem infetados pelo SARS-CoV-2, aumentando o risco de desenvolver ou agravar problemas de saúde mental (5). Questões como fadiga física, stress psicológico, défice de stock ou negligência no uso do equipamento de proteção individual ou de outras medidas de segurança afetaram os médicos, enfermeiros e assistentes (6).…”
Section: Introductionunclassified